2014
DOI: 10.1093/heapro/dau010
|View full text |Cite
|
Sign up to set email alerts
|

Physically active Chilean school kids perform better in language and mathematics

Abstract: SummaryWe examined the association between the engagement in regular physical activity (PA) and the academic performance (AP) of school-age children from Santiago Metropolitan Region. In a random sample of 1271 students (13.3 6 2.3 years old) we measured regular PA, accounting for hours of weekly scheduled exercise, and AP, using national standardized tests scores in Language and Mathematics. Bivariate and multivariate regression analyses were used to model the relation between academic and health-related beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 34 publications
0
12
0
2
Order By: Relevance
“…In Chile, sedentary behaviors seem to be the rule among adolescents. Population‐based study carried out in high schoolers from the Santiago Metropolitan Region reported that 80% of students devote less than 2 h/wk to scheduled exercise . Another study in 16‐year‐old Chilean adolescents found that males and females in the lowest quartile of physical activity had higher risk of obesity, abdominal obesity, and MetS …”
Section: Discussionmentioning
confidence: 99%
“…In Chile, sedentary behaviors seem to be the rule among adolescents. Population‐based study carried out in high schoolers from the Santiago Metropolitan Region reported that 80% of students devote less than 2 h/wk to scheduled exercise . Another study in 16‐year‐old Chilean adolescents found that males and females in the lowest quartile of physical activity had higher risk of obesity, abdominal obesity, and MetS …”
Section: Discussionmentioning
confidence: 99%
“…Our ability to complete physical fitness and physical activity assessments of children and youth with an ASD has additional educational implications. The relationship between academics and physical activity is a current topic of discussion in the United States [ 31 33 ] and federal initiatives aimed at improving the fitness of our youth have been implemented nationwide, with health and education in mind (e.g., Let's Move, Healthy People 2020). Eveland-Sayers et al [ 34 ] investigated physical fitness and academic achievement in elementary school children and found a link between specific components of physical fitness and academic achievement.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…Fiziksel aktivitenin sebep olduğu fizyolojik değişimler fiziksel uygunlukta gelişmeye sebep olur. Fiziksel uygunluk; sağlık ve performans olmak üzere iki bileşenden oluşan ve öğrencilerin genel sağlığını ve dolaylı olarak akademik başarılarını etkileyen bir değişkendir (Correa- Burrows, Burrows, Ibaceta, Orellana ve Ivanovic, 2014). Araştırmalar sağlıkla ilişkili fiziksel uygunluk düzeyindeki artışın bilişsel işlevleri ve uyku kalitesini artırdığını, depresyon, kaygı ve stresi azalttığını ve dolayısı ile akademik başarıyı yükselttiğini göstermektedir (Castelli, Hillman, Buck ve Erwin, 2007;Santana vd., 2017;Tomporowski, Lambourne ve Okumura, 2011).…”
Section: Introductionunclassified